Ca2+/calmodulin-dependent kinase IIδC-induced chronic heart failure does not depend on sarcoplasmic reticulum Ca2+ leak - Dewenter, Matthias; Seitz, Tilmann; Steinbrecher, Julia H.; Westenbrink, B. Daan; Ling, Haiyun; Lehnart, Stephan E.; Wehrens, Xander H.T.; Backs, Johannes; Brown, Joan Heller; Maier, Lars S.; Neef, Stefan (ESC heart failure, 2024)
Aims Hyperactivity of Ca2+/calmodulin-dependent protein kinase II (CaMKII) has emerged as a central cause of pathologic remodelling in heart failure. It has been suggested that CaMKII-induced hyperphosphorylation of the ryanodine receptor 2 (RyR2) and consequently increased diastolic Ca2+ leak from the sarcoplasmic reticulum (SR) is a crucial mechanism by which increased CaMKII activity leads to contractile dysfunction. We aim to evaluate the relevance of CaMKII-dependent RyR2 phosphorylation for CaMKII-induced heart failure development in vivo. Methods and results We crossbred CaMKIIδC overexpressing [transgenic (TG)] mice with RyR2-S2814A knock-in mice that are resistant to CaMKII-dependent RyR2 phosphorylation. Ca2+-spark measurements on isolated ventricular myocytes confirmed the severe diastolic SR Ca2+ leak previously reported in CaMKIIδC TG [4.65 ± 0.73 mF/F0 vs. 1.88 ± 0.30 mF/F0 in wild type (WT)]. Crossing in the S2814A mutation completely prevented SR Ca2+-leak induction in the CaMKIIδC TG, both regarding Ca2+-spark size and frequency, demonstrating that the CaMKIIδC-induced SR Ca2+ leak entirely depends on the CaMKII-specific RyR2-S2814 phosphorylation. Yet, the RyR2-S2814A mutation did not affect the massive contractile dysfunction (ejection fraction = 12.17 ± 2.05% vs. 45.15 ± 3.46% in WT), cardiac hypertrophy (heart weight/tibia length = 24.84 ± 3.00 vs. 9.81 ± 0.50 mg/mm in WT), or severe premature mortality (median survival of 12 weeks) associated with cardiac CaMKIIδC overexpression. In the face of a prevented SR Ca2+ leak, the phosphorylation status of other critical CaMKII downstream targets that can drive heart failure, including transcriptional regulator histone deacetylase 4, as well as markers of pathological gene expression including Xirp2, Il6, and Col1a1, was equally increased in hearts from CaMKIIδC TG on a RyR WT and S2814A background. Conclusions S2814 phosphoresistance of RyR2 prevents the CaMKII-dependent SR Ca2+ leak induction but does not prevent the cardiomyopathic phenotype caused by enhanced CaMKIIδC activity. Our data indicate that additional mechanisms—independent of SR Ca2+ leak—are critical for the maladaptive effects of chronically increased CaMKIIδC activity with respect to heart failure.
Online veröffentlicht: 14. April 2024
Gesehen am 17.04.2025